Leptospirosis in native mixed-breed sheep slaughtered in a semiarid region of Brazil - Costa,Diego Figueiredo da (2017)
ABSTRACT: Sheep breeding is an economic activity of great value for the Brazilian livestock industry, and infectious diseases can significantly compromise its productivity. The aim of this study was to detect Leptospira spp. in mixed breed sheep from a semiarid region of the State of Paraíba, Northeast Brazil. In total, 49 blood and renal tissue samples, as well as 25 urine samples, were collected from 49 sheep in the slaughter line. The microscopic agglutination test (MAT) was used to verify the presence of anti -Leptospira spp. antibodies in blood samples. Renal tissue and urine samples were analyzed by both PCR and bacterial culture. Sero reactivity was observed in 8.2% (4/49) of animals. Three renal samples were positive for leptospiral DNA by PCR although all urine samples were negative. No leptospires in pure culture were recovered from the samples tested. Low prevalence of Leptospira spp. observed by serology and PCR suggested that the rusticity of the mixed-breed sheep may have contributed to the low occurrence of leptospirosis in the semiarid region investigated.